Surviving severe COVID‐19: Interviews with patients, informal carers and health professionals. Issue 1 (13th May 2022) - Gonçalves, Ana‐Carolina; Williams, Annabel; Koulouglioti, Christina; Leckie, Todd; Hunter, Alexander; Fitzpatrick, Daniel; Richardson, Alan; Hardy, Benjamin; Venn, Richard; Hodgson, Luke
Abstract: Background: The COVID‐19 pandemic has been associated with an unprecedented number of critical care survivors. Their experiences through illness and recovery are likely to be complex, but little is known about how best to support them. Aim: This study aimed to explore experiences of illness and recovery from the perspective of survivors, their relatives and professionals involved in their care. Study design: In‐depth qualitative interviews were conducted with three stakeholder groups during the first wave of the pandemic. A total of 23 participants (12 professionals, 6 survivors and 5 relatives) were recruited from 5 acute hospitals in England and interviewed by telephone or video call. Data analysis followed the principles of Reflexive Thematic Analysis. Findings: Three themes were generated from their interview data: (1) Deteriorating fast—a downhill journey from symptom onset to critical care; (2) Facing a new virus in a hospital—a remote place; and (3) Returning home as a survivor, maintaining normality and recovering slowly. Conclusions: Our findings highlight challenges in accessing care and communication between patients, hospital staff and relatives. Following hospital discharge, patients adopted a reframed 'survivor identity' to cope with their experience of illness and slow recovery process. The concept of survivorship in this patient group may be beneficial to promote and explore further. Relevance to clinical practice: All efforts should be made to continue to improve communication between patients, relatives and health professionals during critical care admissions, particularly while hospital visits are restricted. Adapting to life after critical illness may be more challenging while health services are restricted by the impacts of the pandemic. It may be beneficial to promote the concept of survivorship, following admission to critical care due to severe COVID‐19.